Upaya Meningkatkan Hasil Belajar Siswa dengan Menerapkan Model Pembelajaran Example Non Example Tentang Hubungan Makanan dan Kesehatan pada Pelajaran IPA Di Kelas V SD Negeri 140 Bengkulu Utara - Yuliati; Widodo (Kilau Publishing, 2023)
This research aims to determine the influence of students' example non example models in class V science lessons at SDN 140 North Bengkulu. The research subjects were 17 class V students. Data collection was carried out by observation and final learning test. Data analysis was carried out descriptively. The results of the research show that by using the example non example learning model, learning outcomes regarding the relationship between food and health in science lessons in class V of SD Negeri 140 North Bengkulu can be improved. Research data proves this by increasing the average daily test 1 to 63.00 to 70.00, the average daily test 3 to 75.33, and the average daily test 4 to 82.52. The results of this research can be concluded that the use of the example non example model is effective in improving student learning outcomes in science lessons in class V S 140 North Bengkulu.